Rancang Bangun Helm Pendeteksi Kantuk pada Prajurit Menggunakan Pulse Sensor Berbasis Arduino Nano untuk Kesiapsiagaan Prajurit dalam Melaksanakan Tugas - Faisal Dian M; Petrus Gunawan; Rafi Maulana; Dekki Widiatmoko; Aguk Sridaryono (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The preparedness and security of military soldiers is an important aspect of military operations. Fatigue or drowsiness in soldiers can threaten their effectiveness in carrying out critical tasks. This research aims to design and build a smart helmet equipped with an Arduino Nano-based pulse detection sensor to detect early signs of drowsiness in soldiers. The use of this technology is expected to provide early warning to soldiers when worrying signs of fatigue are detected, allowing them to take preventive action or rest before conditions that threaten their safety occur. The methodology used involves the development of a smart helmet, integration of a pulse sensor, real-time data processing, and a responsive warning system. Trials were carried out by simulating field conditions to evaluate the performance of this drowsiness detection helmet. It is hoped that the results of this research can increase the preparedness and safety of soldiers in carrying out military duties.